(untitled) (World Bulletin of Social Sciences, 2024)
This article is about revealing the meaning of ethnocultural realities by translational and non-translational methods. The author refers to the translation method of semantics as translation-interpretation, in which, in addition to the equivalent in their native language, students are informed about the coincidence or discrepancy in the scope of the meaning of lacunae. We are also talking about a non-translational method of semantics, which includes: demonstration of objects, gestures, actions, paintings, drawings, slides, slides and disclosure of the meanings of realities in Russian, for which definitions can be used - descriptions of the meaning of a new word with already known words